Pelatihan Penyusunan Materi Ajar Melalui OBS untuk Meningkatkan Keterampilan Profesional Guru Sekolah Dasar - Imaniar Purbasari; Lintang Kironoratri; Nur Fajrie (J-ABDIPAMAS (Jurnal Pengabdian Kepada Masyarakat), 2023)
ABSTRACTProfessional teachers are teacher who can change and feel challenged by scientific changes and the demands of the times. Teaching materials that are in accordance with learning objectives are packaged creatively, as a form of reflection on the needs of students in the modern area. Training in the preparation of teaching materials through OBS to improve the professional skills of teachers is a solution to learning problems during the pandemic. As a result of this service activity, in the diagnostic stage, it was found the need for innovation in teaching materials that utilize technology. The planning action stage for partners and teams determines the form of power point teaching materials to be developed through OBS software. In the taking action stage, partners and teams carry out activities for compiling digital teaching materials in the form of video recording and live streaming through OBS software. In the evaluating action stage, partners respond positively and enthusiastically to program implementation. The follow-up of the service activities was carried out by mapping materials and developing digital teaching materials to be disseminated to the wider educational community.Keywords: professional, learning resource, open broadcaster softwareABSTRAKGuru yang professional merupakan guru yang mau merubah dan merasa tertantang akan perubahan keilmuan dan tuntutan jaman. Materi ajar yang sesuai dengan tujuan pembelajaran dikemas secara kreatif, sebagai bentuk reflektif kebutuhan peserta didik di era modern. Pelatihan penyusunan materi ajar melalui OBS untuk meningkatkan keterampilan professional guru merupakan solusi terhadap permasalahan pembelajaran selama pandemi. Hasil dari kegiatan pengabdian ini, tahapan diagnosing ditemukan perlunya inovasi materi ajar yang memanfaatkan teknologi. Tahap planning action mitra dan tim menentukan bentuk materi ajar power point untuk dikembangkan melalui software OBS. Tahapan taking action, mitra dan tim melakukan kegiatan penyusunan materi ajar digital berupa video recording dan live streaming melalui software OBS. Tahapan evaluating action, mitra merespon secara positif dan antusias pelaksanaan program. Tindak lanjut dari kegiatan pengabdian dilakukan pemetaan materi dan pengembangan materi ajar digital untuk didesiminasikan pada masyarakat pendidikan secara luas.Kata Kunci: profesionalisme guru, materi ajar, open broadcaster software